Challenges and opportunities in Nigeria’s home-grown school feeding program: Toward a more efficient and sustainable model - Adeyanju, Dolapo; Amare, Mulubrhan; Andam, Kwaw S.; Bamiwuye, Temilolu; Gelli, Aulo; Idowu, Ifetayo (International Food Policy Research Institute, 2024)
This paper examines Nigeria’s Home-Grown School Feeding Program (HGSFP), an initiative that enhances traditional school feeding by supporting local agriculture. Operating across federal, state, and school levels, the HGSFP sources meals from local smallholder farmers, aiming to stimulate rural economies and improve food security. The program creates demand for locally grown food, encouraging farmers to increase productivity and adopt sustainable practices while providing them with stable income.